“El beneficio de separación y sus efectos jurídicos en los juicios de apertura de sucesión y partición tramitados en el juzgado segundo de lo civil y mercantil del cantón Riobamba en el periodo 2007 - 2013” - Asadobay Tayupanda, Noemi Alexandra (2016)
This research seeks to address the analysis of process of civil processes and problems to show that it is essential to reform the prevailing constitutional principles of due process speed and efficiency, without compromising the right of the parties through methodological, consistent and rigorous criteria that explain the variables and other elements of reality, which have impeded the implementation of the institution in comment despite the high real yield that it should be legal practice and the specific resolution a significant portion of the conflicts generated by the incorrect application of a legal concept. The conclusions reached are to draw the attention of legislators and legal theorists to legislate, develop and specify appropriate for this important institution is applied criteria operators. The research served to reaffirm the knowledge instilled in the civil field and to get an idea of how justice in the country is run. Thus, the present investigation is fully justified given that the description, explanation and understanding of the problems of the legal institution to which it relates, we believe it will bring great practical benefits regarding the resolution of the civil conflict, which at the same time will result in the legitimization of the justice administration in the society.